PERSEPSI GURU TERHADAP EFEKTIVITAS PENGGUNAAN E-RAPOR DI SMA NEGERI 1 AMPEK ANGKEK, KABUPATEN AGAM - Muhammad Jaffar; Ahmad Sabandi (Universitas Negeri Padang, 2019)
This study aims to determine the effectiveness of the use of e-report by teachers at High School (SMA) Negeri 1 Ampek Angkek, Agam. This research is a descriptive study with a quantitative approach. The population of this study were all teachers who served as civil servants totaling 70 people. While the sampling technique in this study uses a total sample with the number of samples equal to the population. The data collection technique is through questionnaires with Likert scale models that have been tested for validity and reliability. The results of the study show the effectiveness of the use of e-report by teachers at SMA Negeri 1 Ampek Angkek, Agam can be said to be effective. This can be seen from the average score obtained per indicator which shows that the system quality indicator gets a score of 3.49 with a fairly effective category, the information quality indicator scores 3.74 with the effective category, the service quality indicator 3.79 with the category effective, usage satisfaction indicators get a score of 3.81 with effective categories, and profit indicators that get a score of 4.03 in the effective category. So the use of e-report by the teacher at SMA Negeri 1 of Ampek Angkek, Agam can be declared effective by getting an average score of 3.77.